Nanoprecipitation effects on phase stability of Fe-Mn-Al-Ni alloys - la Roca, Paulo Matías (2017)
Early stages of coherent precipitation have been studied in several Fe-Mn-Al-Ni samples aged at 200 °C for different time intervals in order to analyze the effect of nanoprecipitation on the phase stability during thermally induced martensitic transformations. The α-γ′ martensitic transformation was studied by means of dilatometry measurements. Transmission electron microscopy (TEM) observations were performed in order to characterize the microstructure of the samples. The size and volume fraction of nanoprecipitates were evaluated for the as-quenched material and samples aged for 10, 20 and 180 min. Considering these data and additional high resolution TEM results reported in the literature a phenomenological model is presented that enables understanding the effects of B2 precipitates on the relative phase stability between austenite and martensite, and their influence on the observed pseudoelasticity of this metallic system. With this model, the changes of the measured transformation temperatures can be predicted with considerable accuracy.